THE IMPORTANCE OF COMMUNITY COALITION TO PREVENT DENGUE FEVER: AN ETHNOGRAPHIC STUDY IN SIDOLUHUR VILLAGE, SLEMAN DISTRICT, YOGYAKARTA SPECIAL REGION, INDONESIA - , RANA, SOHEL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background Dengue fever is a pandemic-prone viral disease in many parts of the world also in Indonesia. Java Island contributed about 71% of all cases occurring in the country. Sleman District represented highest 30% of total infections in Yogyakarta Province among the neighboring districts. Cases are increasing every year though they have some program like Friday cleaning, mosquito larvae eradication and child health task force. Vector control is one of the ways to control it where every concern group needs to participate. Community coalition can prevent dengue fever by engaging all stakeholders like community people, community leader, health worker and government health officials. Methods: This research was using ethnographic study. In-depth interview, participatory observation and FGD were conducted for data collection. Results: Dengue fever is a serious health problem among the people in study area. A big number of people are not able to indentified dengue fever where they define fever by their local term. Getting well from dengue people use cultural and medical health seeking system where cultural seeking behavior gets priority. For eradicating dengue mosquito community has some program like Friday cleaning movement, mosquito larvae eradication and child health task force. Informationâs about dengue fever are not available in study area. Nearby public health center has a program called awareness building program through health worker where health worker learn from health center and spread it among the people. Conclusion: Dengue fever remains a strong factor that influences public health care in Sidoluhur village. To control dengue fever capacity building, policy implementation based on community networking among stakholders, blending the cultural and medical knowledge of dengue and overall comprehensive dengue control approaches need to be developed.